Phonological Classification of Arabic Based on Articulatory Similarities with Indonesian: A Comparative Linguistic Study - Ulum, Muhammad Bachrul (Journal of Arabic Language Studies and Teaching, 2024)
This study is an attempt to provide an alternative solution to a common issue at the foundational level of Arabic language learning, namely letter recognition. For non-native speakers, articulation often poses a significant challenge, and misarticulation can lead to numerous subsequent problems related to speaking and listening skills. This research compares the phonology of Arabic and Indonesian letters to develop instructional materials for beginner-level Arabic learners. The study employs a qualitative method based on a comparative approach, analyzing the articulation of each letter in both languages. The findings indicate that the teaching of Arabic letter articulation to Indonesian speakers should begin with groups of letters that have identical articulation, followed by groups with similar articulation, and finally, those with distinct articulation.